Cryopreservation of seeds from the endangered insectivorous plant Drosophyllum lusitanicum - Gonçalves, Sandra (2013)
The aim of the present work was to explore the feasibility of seed cryopreservation as a tool for Drosophyllum lusitanicum genetic resources preservation. Mature seeds, collected from a wild Portuguese population, were used in different cryopreservation treatments and their germination rates assessed in vitro. No germination was observed when seeds were directly plunged into liquid nitrogen (LN) without any drying pre-treatment. When seeds were dried, immersed in LN during 30 min and rapidly warmed, germination rate increased to 94%. Cryopreserved seeds were stored for 4 months at -18°C without losing germination capacity. The feasibility of cryopreserving mature seeds of D. lusitanicum was verified in this work demonstrating that cryopreservation, alone or combined with conventional storage at -18°C, can be used as a complementary strategy for the longterm storage of germplasm of this endangered species.